2020
DOI: 10.3390/cells9122576
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Hormones and Several Abiotic Stress Conditions on Arabidopsis thaliana Primary Root Development

Abstract: As sessile organisms, plants must adjust their growth to withstand several environmental conditions. The root is a crucial organ for plant survival as it is responsible for water and nutrient acquisition from the soil and has high phenotypic plasticity in response to a lack or excess of them. How plants sense and transduce their external conditions to achieve development, is still a matter of investigation and hormones play fundamental roles. Hormones are small molecules essential for plant growth and their fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 307 publications
1
17
0
Order By: Relevance
“…Exogenous hormones play an important role in stimulating plant growth under various biotic and abiotic stresses, but little is known about the relationship of exogenous hormones to their endogenous concentrations [ 91 ]. Our tests showed that the application of exogenously hormones as well as endophytic extracts had varying effects on the hormonal content of the common bean plants, and some of these treatments caused a significant increase in the hormonal content of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous hormones play an important role in stimulating plant growth under various biotic and abiotic stresses, but little is known about the relationship of exogenous hormones to their endogenous concentrations [ 91 ]. Our tests showed that the application of exogenously hormones as well as endophytic extracts had varying effects on the hormonal content of the common bean plants, and some of these treatments caused a significant increase in the hormonal content of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…Plants cope with environmental changes by reprogramming gene expression and metabolic processes necessary for growth, development, and survival (e.g., Hirayama and Shinozaki, 2010 ; Sewelam et al, 2014 ; Lopez-Ruiz et al, 2020 ). The adaptability of a genotype to changing environmental conditions is therefore determined by its genome and gene activity, both of which are in turn influenced by epigenetic factors such as DNA methylation (e.g., Dowen et al, 2012 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant roots show high phenotypic plasticity in response to insufficient or excessive nutrient resources ( López-Ruiz et al, 2020 ). Here, we observed root developmental phenotypes under four different nitrogen conditions ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%